Charge transfer dynamics in chlorophyll-based biosolar cells. Issue 40 (7th October 2019) - Zhao, Wenjie; Wang, Li; Pan, Lingyun; Duan, Shengnan; Tamai, Naoto; Sasaki, Shin-ichi; Tamiaki, Hitoshi; Sanehira, Yoshitaka; Wei, Yingjin; Chen, Gang; Wang, Xiao-Feng
Abstract : The charge dissociation and transfer could occur at the interface of both chlorophyll species in chlorophyll-based bio-solar cells. Abstract : We fabricated a chlorophyll (Chl)-based biosolar cell with H2 Chl-sensitized TiO2 as an acceptor and (ZnChl) n as a donor. This solar cell gives a relatively high quantum yield from the absorption spectral contribution from both the donor and acceptor species. We employed subpicosecond time-resolved absorption spectroscopy (TAS) to study the excited state dynamics at the Chl interface. A charge transfer (CT) state between TiO2 –H2 Chl and (ZnChl) n was observed at 640 nm after excitation at the Q y peaks, 680 nm and 720 nm. This CT state is entirely different from the CT states observed for either TiO2 –H2 Chl (TiO2 –H2 Chl/spiro-OMeTAD) or TiO2 –(ZnChl) n systems. Due to the slower charge transfer process from H2 Chl + to TiO2 as compared to that from (ZnChl) n + to H2 Chl, the CT lifetimes of H2 Chl − –(ZnChl) n + ( τ 1 = 0.1 ps, τ 2 = 1.4 ps) excited at 720 nm are slightly shorter than that excited at 680 nm ( τ 1 = 0.2 ps, τ 2 = 5.6 ps). The TAS results suggest that the interface of TiO2 –H2 Chl and (ZnChl) n not only transfers holes as spiro-OMeTAD does, but also provides a built-in field for charge dissociation between the two Chl species.